Attribute-based multi-keyword searchable encryption scheme based on counting Bloom filters - Zhidan LI; Yongqun CHEN; Wei WANG (Dianxin kexue)
To address the problems of low retrieval efficiency of searchable encryption scheme under traditional public key cryptosystem, high storage overhead of keyword index, and index does not support dynamic update, based on the good space and time efficiency of counting Bloom filter to determine whether an element belongs to a certain set, the feature into searchable encryption was applied to establish keyword index, thus, the keyword set was mapped into a binary vector, thereby reducing the keyword storage cost.Simultaneously, the feature of counting Bloom filter can be deleted was used to realize the dynamic update of keyword index.In addition, to prevent adversaries from inferring keyword plaintext information from binary vectors through statistical analysis, the binary vector was blinded by permutation, and then the permutation was encrypted by attribute-based encryption for secret sharing.After legitimate users generated keyword traps correctly, the service provider helped users complete keyword matching queries based on the user’s keyword trapdoor.Finally, the security and efficiency of the scheme were proved through security analysis and simulation experiments.